BIJAK MENGGUNAKAN ANTIBIOTIK DI DESA TUNGKARAN PANGERAN KABUPATEN TANAH BUMBU - Nur Mahdi; Deni Setiawan (Jurnal Abdi Masyarakat Kita, 2021)
The current problem that occurs is the increased use of antibiotics freely and mistakenly causing antibiotics to become resistant to bacteria as well as inappropriate storage which causes the antibiotic to be damaged so that their effectiveness is lost. A Survey that started in the village of Tungkaran Pangeran, Tanah Bumbu district identified that there is a lack of public knowledge about the use of antibiotics. It also found mistakes in storing drugs, especially antibiotics. The output target of community service activities is to increase community knowledge about antibiotics from the understanding, classification, storage, and resistance of antibiotics. Besides, the public also understands the regulation of getting the right antibiotic in Indonesian. As a result of community service activities in Tungkaran Pangeran Village, Tanah Bumbu District, there has been a significant increase in community knowledge on the proper and correct use and storage of antibiotics